Antibody Responses to Antigenic Sites 1 and 3 of Serotype 3 Poliovirus after Vaccination with Oral Live Attenuated or Inactivated Poliovirus Vaccine and after Natural Exposure - Herremans, T. (American Society for Microbiology, 2000)
Three important antigenic sites involved in virus neutralization on polioviruses in mouse experiments have been identified. These sites are located at the surface of the virion and have been designated antigenic sites 1, 2, and 3. In mice, the antibody response to antigenic site 1 of serotype 3 poliovirus is considered to be immunodominant, but little is known about the immunogenicity of these sites in humans. In the present study, we developed inhibition enzyme-linked immunosorbent assays specific for antigenic sites 1 and 3 to measure antibody responses to these sites in fully vaccinated inactivated poliovirus vaccine (IPV) (n = 63) and oral live attenuated poliovirus vaccine (OPV) (n = 63) recipients and in naturally infected persons (n = 25). Similar levels of antibodies to site 1 in IPV and OPV vaccinees were detected. However, significantly more OPV recipients (88.7%) had detectable antibodies to antigenic site 3 (P < 0.01) than did IPV-vaccinated persons (63.1%). After an IPV booster vaccination, both previously IPV- and OPV-vaccinated persons responded with a significant increase in antibodies to sites 1 and 3 (P < 0.01). We conclude that the immune response to serotype 3 poliovirus in humans consists of both site 1- and site 3-specific antibodies and that these responses can be induced by either OPV or recent IPV vaccination.